PELAKSANAAN UPACARA ADAT PERKAWINAN (KIET FUN) PADA MASYARAKAT TIONGHOA HAKKA DI KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - NIM. A1011211127, VIVI CINTIA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Kiet Fun is a traditional marriage ceremony in the Hakka Chinese community that is rich in symbolism and cultural values that are passed down from generation to generation reflecting the hope for life after marriage and respect for ancestors, but at this time in the implementation of the traditional marriage ceremony (kiet fun) there has been a shift that causes changes in its implementation. The formulation of the problem in this study is